2002
DOI: 10.1021/bi026105r
|View full text |Cite
|
Sign up to set email alerts
|

Tail-Anchored Protein Insertion into Yeast ER Requires a Novel Posttranslational Mechanism Which Is Independent of the SEC Machinery

Abstract: Tail-anchored or C-terminally-anchored proteins play many essential roles in eukaryotic cells. However, targeting and insertion of this class of membrane protein has remained elusive. In this study, we reconstitute insertion of tail-anchored proteins into microsomes derived from Saccharomyces cerevisiae. Using this approach, we are able to genetically manipulate the composition of the microsomes in order to address the question of which components of the endoplasmic reticulum (ER) are required for this process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…Bioinformatic analyses suggest that up to 5% of predicted integral membrane proteins in eukaryotic genomes may follow this SRP-independent route including the large class of SNARE proteins that drive intracellular membrane fusion events and are anchored by C-terminal membrane domains. Interestingly, this post-translational targeting pathway operates independently of the Sec61 and Sec63 translocon complexes (Steel et al 2002;Yabal et al 2003) and instead depends on recently defined soluble and membrane-bound factors. Large-scale genetic interaction analyses in yeast identified a clustered set of nonessential genes that produced Golgi-to-ER trafficking deficiencies that were named GET genes (Schuldiner et al 2005).…”
Section: Polypeptide Targeting and Translocationmentioning
confidence: 99%
“…Bioinformatic analyses suggest that up to 5% of predicted integral membrane proteins in eukaryotic genomes may follow this SRP-independent route including the large class of SNARE proteins that drive intracellular membrane fusion events and are anchored by C-terminal membrane domains. Interestingly, this post-translational targeting pathway operates independently of the Sec61 and Sec63 translocon complexes (Steel et al 2002;Yabal et al 2003) and instead depends on recently defined soluble and membrane-bound factors. Large-scale genetic interaction analyses in yeast identified a clustered set of nonessential genes that produced Golgi-to-ER trafficking deficiencies that were named GET genes (Schuldiner et al 2005).…”
Section: Polypeptide Targeting and Translocationmentioning
confidence: 99%
“…However, despite such circumstantial evidence (Fig. 2), there is currently no functional data to support a role for the Sec61 translocon during the membrane integration of Syb2 (Kutay et al, 1995) or of any other tail-anchored protein (Steel et al, 2002;Yabal et al, 2003). Thus, the molecular basis for the membrane integration of tail-anchored proteins that are delivered to the ER via a post-translational SRP-mediated pathway is unknown (Fig.…”
Section: Lipidmentioning
confidence: 99%
“…In vitro studies have indicated that the post-translational biogenesis of most, if not all, tail-anchored proteins is stimulated by ATP (Abell et al, 2007;Favaloro et al, 2008;Kim et al, 1999;Kim et al, 1997;Kutay et al, 1995;Steel et al, 2002;Yabal et al, 2003) and the participation of at least one ATP-dependent cytosolic factor in this process was suggested several years ago (Yabal et al, 2003). Certain secretory proteins are translocated across the ER membrane by an unusual post-translational mechanism involving cytosolic members of the Hsp70 family of molecular chaperones (Ngosuwan et al, 2003;Zimmermann, 1998); by extrapolation, it is possible to speculate that such chaperones play a similar role during biogenesis of tail-anchored proteins (Box 2).…”
Section: Hsp40-hsc70-mediated Pathway Of Er Integrationmentioning
confidence: 99%
“…6). Current models range from those that suggest the process maybe entirely lipid dependent (Brambillasca et al, 2006) move through those that conclude novel integration sites may be used (Steel et al, 2002;Yabal et al, 2003), and include the possibility that the well-defined Sec61 translocon may mediate integration (Abell et al, 2003). The in vivo role of Hsc70-Hsp40 chaperones during TA protein biogenesis and the identity of any ER specific receptors for these components are a key questions for future studies.…”
Section: Sec61 G Syb2mentioning
confidence: 99%